Global issues, local practices: Possibilities in Brazilian initial and continuing English teaching education - Hibarino, Denise Akime; Nodari, Janice Ines (Argentinian Journal of Applied Linguistics - ISSN 2314-3576, 2022)
This paper aims to present the PIBID (Institutional Scholarship Program for Teacher Initiation) - a partnership programme proposed by MEC (the Ministry of Education in Brazil) and implemented by universities and public state schools throughout Brazil - by describing some of its actions regarding the teaching of the English language. The PIBID - English UFPR focuses on initial and continuing education of English teachers in a partnership between the local public state schools and the federal university, and it is informed by assumptions provided by a critical literacy framework (Cope, Kalantzis, 2000; Gee, 2000; Jordão, 2013a, 2013b; Jordão et al, 2013b), on the concept of English as an International Language (Jenkins, 2007; 2010; McKay, 2003; Sharifian, 2009), along with the regulatory Brazilian educational official documents.